A Nonsense Variant in the ST14 Gene in Akhal-Teke Horses with Naked Foal Syndrome. Issue 4 (1st April 2017) - Bauer, Anina; Hiemesch, Theresa; Jagannathan, Vidhya; Neuditschko, Markus; Bachmann, Iris; Rieder, Stefan; Mikko, Sofia; Penedo, M Cecilia; Tarasova, Nadja; Vitková, Martina; Sirtori, Nicolò; Roccabianca, Paola; et al.
Abstract: Naked foal syndrome (NFS) is a genodermatosis in the Akhal-Teke horse breed. We provide the first scientific description of this phenotype. Affected horses have almost no hair and show a mild ichthyosis. So far, all known NFS affected horses died between a few weeks and 3 yr of age. It is not clear whether a specific pathology caused the premature deaths. NFS is inherited as a monogenic autosomal recessive trait. We mapped the disease causing genetic variant to two segments on chromosomes 7 and 27 in the equine genome. Whole genome sequencing of two affected horses, two obligate carriers, and 75 control horses from other breeds revealed a single nonsynonymous genetic variant on the chromosome 7 segment that was perfectly associated with NFS. The affected horses were homozygous for ST14 :c.388G>T, a nonsense variant that truncates >80% of the open reading frame of the ST14 gene (p.Glu130*). The variant leads to partial nonsense-mediated decay of the mutant transcript. Genetic variants in the ST14 gene are responsible for autosomal recessive congenital ichthyosis 11 in humans. Thus, the identified equine ST14 :c.388G>T variant is an excellent candidate causative variant for NFS, and the affected horses represent a large animal model for a known human genodermatosis. Our findings will enable genetic testing to avoid the nonintentional breeding of NFS-affected foals.